LSB Substitution and PVD performance analysis for image steganography - SOLAK, Serdar; ALTINIŞIK, Umut (International Journal of Computer Sciences and Engineering, 2018)
Image Steganography is data hiding technology to transmit securely significant data in an open channel. In this paper, we present performance analysis of Least Significant Bit (LSB) substitution and Pixel-Value Differencing (PVD) methods commonly used in image steganography. The comparison of these methods is performed by using Peak Signal-toNoise Ratio (PSNR), Structural Similarity Index (SSIM) and payload values. The 512 x 512 size of colored and gray-scale cover images as Lena, Baboon, Peppers, and Airplane are used in the experimental studies. In the LSB method, the PSNR values are about 51.6, while the PVD method is between 37.83 and 41.28 for colored cover image. In gray-scale images, while PVD is between 38.52 and 41.42, the LSB is about 51.14. In our paper results shows that PSNR and SSIM values are higher in LSB substitution than PVD method. However, PVD method embeds more secret data than LSB substitution method into cover image with less visual perceptibility.